PEMANFAATAN RUANG PUBLIK PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI TROTOAR JL PANJAITAN KOTA GORONTALO - Dewinta Rizky R. Hatu; Sahrain Bumulo; Fitrah Bau (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2026)
This study examines the utilization of public space by Micro, Small, and Medium Enterprises (MSMEs) along the sidewalks of Jalan Panjaitan in Gorontalo City. The phenomenon reflects a transformation in the function of sidewalks, which were initially intended for pedestrian facilities but later evolved into social and economic spaces within urban society. The research aims to analyze the patterns of public space utilization by MSME actors and the forms of social interaction emerging within the area. The study applies a descriptive qualitative method using a case study approach. Data collection techniques were conducted through interviews, observations, and documentation involving MSME actors, local residents, visitors, and related government institutions. Data analysis was carried out through stages of data reduction, data presentation, and conclusion drawing by applying Jürgen Habermas’s public sphere theory perspective. The findings indicate that the sidewalks of Jalan Panjaitan are occupied by approximately 50 business units, including coffee vendors, snack sellers, fried rice traders, meatball vendors, flower merchants, and cake sellers. The presence of MSMEs not only contributes economic benefits to the community but also encourages social interactions that make the area more vibrant, particularly during nighttime activities. Nevertheless, these activities also affect the primary function of the sidewalks by reducing pedestrian comfort and increasing congestion within the area.